1995
DOI: 10.1007/s001250050284
|View full text |Cite
|
Sign up to set email alerts
|

Glucose entry into rat mesangial cells is mediated by both Na+-coupled and facilitative transporters

Abstract: Summary Since previous studies from our laboratory have demonstrated that increased glucose consumption by cultured rat mesangial cells is accompanied by an accelerated production of type IV and type VI collagen, we have now examined the manner by which glucose is transported into these cells. A progressive stimulation of glucose uptake by the mesangial cells was observed with increasing concentrations of NaC1 so that at 145 mmol/1 about twice as much glucose entered the cells as in its absence (substituted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…To confirm this finding, we varied the activity of SGLT1 by exposing the enterocytes to different extracellular [Na + ] [15,16], an approach used successfully in rat mesangial cells and in renal brush-border vesicles of an early teleost [6,14]. We employed media with [Na + ] of 0.5, 100.5 or 130.5 mM; the [Na + ] could not be reduced further because Na-β-hydroxybutyrate is an essential requirement for enterocytes.…”
Section: Resultsmentioning
confidence: 63%
“…To confirm this finding, we varied the activity of SGLT1 by exposing the enterocytes to different extracellular [Na + ] [15,16], an approach used successfully in rat mesangial cells and in renal brush-border vesicles of an early teleost [6,14]. We employed media with [Na + ] of 0.5, 100.5 or 130.5 mM; the [Na + ] could not be reduced further because Na-β-hydroxybutyrate is an essential requirement for enterocytes.…”
Section: Resultsmentioning
confidence: 63%
“…It is not yet known whether any of the other, more novel glucose transporters, including GLUT11, are expressed in glomerular cells. Finally, one group has identified sodiumglucose cotransporter (SGLT) activity in cultured mesangial cells [13]. However, there have been no additional studies reported to suggest that sodium-coupled glucose transport plays a major role in glucose uptake and metabolism in mesangial cells in culture or in vivo.…”
Section: Glomerular Facilitative Glucose Transporters In Diabetesmentioning
confidence: 98%
“…GLUT1 is the major facilitative glucose transporter in the glomerular mesangial cell [124]. Its overexpression in these cells creates a diabetic phenotype that includes features of excessive extracellular matrix production even when the cells were cultured under normoglycemic conditions [125,126].…”
Section: Glucose Transporter 1 (Glut1)mentioning
confidence: 99%